2015
DOI: 10.1071/mf14023
|View full text |Cite
|
Sign up to set email alerts
|

The migration behaviour of European silver eels (Anguilla anguilla) released in open ocean conditions

Abstract: Despite some recent progress, there are still large gaps of knowledge about migration routes and behaviour of European eels, Anguilla anguilla, during their long-distance oceanic migration. To achieve a better understanding of the migration behaviour, 28 large female silver eels were equipped with pop-up satellite transmitters and released at three different locations in the north-eastern Atlantic Ocean and in the Sargasso Sea. The study covers tracking periods between 7 and 92 days. The distance between relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…In fact, as a whole, sharks spent more time in warmer water during deep occupation periods in winter as they moved south than they did during summer. While the function of this deep occupation is unknown, the Sargasso Sea is a relatively stable, warm water mass during winter months and may host prey opportunities for basking sharks in the mesopelagic, including a substantial deep scattering layer that overlaps with basking shark depth use (400-600 m; Irigoien et al, 2014) and potentially co-occurring anguillid eel spawning aggregations (Wysujack et al, 2015). These migrations away from the northern winter may also be associated with hotspots of relatively high production at lower latitudes (e.g., Brazilian shelf; Mourato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as a whole, sharks spent more time in warmer water during deep occupation periods in winter as they moved south than they did during summer. While the function of this deep occupation is unknown, the Sargasso Sea is a relatively stable, warm water mass during winter months and may host prey opportunities for basking sharks in the mesopelagic, including a substantial deep scattering layer that overlaps with basking shark depth use (400-600 m; Irigoien et al, 2014) and potentially co-occurring anguillid eel spawning aggregations (Wysujack et al, 2015). These migrations away from the northern winter may also be associated with hotspots of relatively high production at lower latitudes (e.g., Brazilian shelf; Mourato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, hard to avoid the conclusion that, at least for the frequent rapid vertical excursions that we have described in our study, the swim bladder has little or no function for buoyancy regulation of the eel diving behaviour. By release of tagged and assumed infected eels at different points in the Atlantic Wysujack, Westerberg, et al (2014) came to a similar conclusion on the potential impact of A. crassus on diving performance in oceanic depths.…”
Section: Anguillicola Crassus and Swim Bladder Functionmentioning
confidence: 58%
“…By release of tagged and assumed infected eels at different points in the Atlantic Wysujack, Westerberg, et al. () came to a similar conclusion on the potential impact of A. crassus on diving performance in oceanic depths.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, the eels undergo daily vertical migrations of ~500 m. As different eel species appear to swim deeper during full moon than during new moon (Chow et al 2015;Schabetsberger et al 2013), this behavior is likely an attempt to minimize the light environment as this may affect important reproductive hormones (Liu et al 2014;Burgerhout et al 2018) or simply minimize the chance of being spotted by predators (Righton et al 2016;Wahlberg et al 2014). However, the daily vertical migration could also be implemented as a mean of controlling the thermal environment as eel at later stages of migration appear to dive even deeper during the day, where they reach similar temperatures (~10 °C) as those experienced during early migration (Wysujack et al 2015). This behavior may explain peculiar early findings, that eel eyes not only increase before migration but continues to increase during migration and maturation (Boëtius and Boëtius 1967 and Chapter 1).…”
Section: European Eel Life Cyclementioning
confidence: 99%
“…Another environmental factor which might influence eel maturation is the light regime. During continental migration, eels appear to prefer low light environments (Righton et al 2016;Aarestrup et al 2009;Wysujack et al 2015;Lennox et al 2018;Chow et al 2015). Based on this behavior it has been suggested that light should be considered as a factor involved in eel maturation and even the earliest documented eel reproduction experiments hypothesized about the importance of light for eel maturation (Fontaine 1936).…”
Section: Natural Eel Sexual Maturation Factorsmentioning
confidence: 99%